IRON ISOTOPE FRACTIONATION DURING MICROBIALLY STIMULATED FE(II) OXIDATION AND FE(III) PRECIPITATION - Balci N.; Bullen T.D.; Witte-Lien K.; Shanks W.C.; Motelica M.; Mandernack K.W. (My University, 2006)
Interpretation of the origins of iron-bearing minerals preserved in modern and ancient rocks based on measured iron isotope ratios depends on our ability to distinguish between biological and non-biological iron isotope fractionation processes. In this study, we compared 56Fe/54Fe ratios of coexisting aqueous iron (Fe(II)aq, Fe(III)aq) and iron oxyhydroxide precipitates (Fe(III)ppt) resulting from the oxidation of ferrous iron under experimental conditions at low pH (<3). Experiments were carried out using both pure cultures of Acidothiobacillus ferrooxidans and sterile controls to assess possible biological overprinting of non-biological fractionation, and both SO42- and Cl- salts as Fe(II) sources to determine possible ionic/speciation effects that may be associated with oxidation/precipitation reactions. In addition, a series of ferric iron precipitation experiments were performed at pH ranging from 1.9 to 3.5 to determine if different precipitation rates cause differences in the isotopic composition of the iron oxyhydroxides. During microbially stimulated Fe(II) oxidation in both the sulfate and chloride systems, 56Fe/54Fe ratios of residual Fe(II)aq sampled in a time series evolved along an apparent Rayleigh trend characterized by a fractionation factor ?Fe(III)aq-Fe(II)aq?1.0022. This fractionation factor was significantly less than that measured in our sterile control experiments (?1.0034) and that predicted for isotopic equilibrium between Fe(II)aq and Fe(III)aq (?1.0029), and thus might be interpreted to reflect a biological isotope effect. However, in our biological experiments the measured difference in 56Fe/54Fe ratios between Fe(III)aq, isolated as a solid by the addition of NaOH to the final solution at each time point under N2-atmosphere, and Fe(II)aq was in most cases and on average close to 2.9? (?Fe(III)aq-Fe(II)aq ?1.0029), consistent with isotopic equilibrium between Fe(II)aq and Fe(III)aq. The ferric iron precipitation experiments revealed that 56Fe/54Fe ratios of Fe(III)aq were generally equal to or greater than those of Fe(III)ppt, and isotopic fractionation between these phases decreased with increasing precipitation rate and decreasing grain size. Considered together, the data confirm that the iron isotope variations observed in our microbial experiments are primarily controlled by non-biological equilibrium and kinetic factors, a result that aids our ability to interpret present-day iron cycling processes but further complicates our ability to use iron isotopes alone to identify biological processing in the rock record. ? 2005 Elsevier Inc. All rights reserved.
Keywords: IRON; ISOTOPIC FRACTIONATION; PRECIPITATION (CHEMISTRY)